Computer aided process planning based on hybrid decision strategy - Zhong-Bin Wang; Chao Tan; Xiao-Jun Dong (2009 International Conference on Machine Learning and Cybernetics, 2009)
In order to develop dynamic process planning system that can provide dynamic process plans to increase flexibility in workshop, an intelligent CAPP system based on hybrid decision making was investigated. Manufacturing feature sequence and process operation of the old parts in the case library were obtained by the two stage case searching. For the sake of gaining process plans in accord with production conditions in the workshop, manufacturing resource decision was studied in the process of integrating computer aided process planning and production plan and control system, and it was resolved by use of BP neural network and the relevant algorithm to improve the dynamic adaptability of CAPP. It is shown that the hybrid decision making which includes case-based searching and dynamic decision making of manufacturing resource not only retains the practicability of CAPP but also improves its flexibility and dynamic adaptability. Based on an illustrative example, the work mechanism of intelligent CAPP based on hybrid decision making was described.